G449(P) Neurodisability with severe restriction of mobility is associated with reduced serum creatinine levels. (24th May 2017) - Lim, C; Watson, L; Eisenhut, M
Abstract : Aims: It is known that serum creatinine levels are dependent on muscle mass. Our aim was to investigate whether reduced mobility, which is associated with reduced muscle mass, is associated with a reduction in serum creatinine in otherwise well children with neurodisability compared with healthy controls. Methods: We retrospectively extracted data from a physiotherapy data base on children above 2 years of age on age, gender, treatment with medication, co-morbidities and category of Gross Motor Function Classification System (GMFCS) score and creatinine level done when the child was well (outpatient department) and age matched controls. We excluded children on nephrotoxic drugs and with renal disease. We compared creatinine values in children of the following three groups: GMFCS 1, 2 or 3 (group I), GMFCS 4 or 5 (group II), and healthy controls (group III). Results: A total of 137 children were included: A total of 25 children in group I, 65 in group II and 48 in group III. Age and gender were not different between groups. Creatinine levels were signifiantly different between groups (p=0.007 by ANOVA) with patients in group I and III having with a mean creatinine of 35 (SD 9) and 34 micromol/l (SD 9) respectively a signifiantly higher creatinine compared with children from group II with a mean creatinine of 29 (SD 9). Conclusions: Children with neurodisability with mobility restriction requiring physical assistance or powered mobility in most or all settings (GMFCS 4 or 5) have a significantly lower serum creatinine compared with children with milder forms of neurodisability or healty controls and may need a lower reference range for creatinine to enable accurate categorisation of the glomerular filtration rate.